UG06 Implementation of targeted testing and resistance-guided therapy for Mycoplasma genitalium in a large urban STI service. (16th June 2022) - Mitchell, Eilidh; Amin, Omar; Mason, Mark; Gunson, Rory; Winter, Andrew
Abstract : Introduction: Scaling up testing and resistance-guided management for M. genitalium requires attention to case selection and timely and accurate results management. We describe our experience of biomedical scientist-initiated test requesting. Methods: We implemented M. genitalium testing in our local laboratory from 28/6/2021 using the ResistancePlus® MG assay (SpeeDx Ltd). To ensure testing was performed in appropriate cases our biomedical scientist coded forms for M. genitalium once non-gonococcal urethritis was demonstrated by Gram stain. Clinicians could order tests in suspected pelvic infection, contacts and for test of cure. New results messages were developed for the laboratory information system. We examined outcomes in the first 12 weeks by case note review. Results: Between 28/6/2021 and 21/09/2021 164 patients were found to have non-gonococcal urethritis, of whom 160 (98%) underwent M. genitalium testing. Clinicians requested a further 43 tests for other indications. Among 203 tests, 25 (12%) were positive, all on urine samples, with 9 (36%) predicted to have azithromycin resistance. All symptomatic patients received doxycycline. Second antibiotic choice was correct in all patients, with one person uncontactable, and prescribed a mean of 10 days after testing. Only 15 (60%) of patients returned for a test of cure (TOC) but all these had cleared infection. Only half of those treated for pelvic infection were tested for M. genitalium. Discussion: Our biomedical scientist-supported reflex testing was effective. Well-designed electronic results handling and training contributed to good antibiotic stewardship. We plan to move to self-sampling for TOC and improve uptake in suspected pelvic infection.